Rippling Outwardly: Archives With Augmented And Mixed Reality - Jeannette Ginslov (The International Journal of Screendance, 2022)
In this article I propose that augmented reality (AR) and mixed reality (MR) have the potential to expand the notion of a Screendance archive. This takes the form of a hybrid installation, where visitors are invited to download an AR app onto their mobile phones, or tablets, to access a Screendance archive tagged to images in an installation space. This type of archive, is conceived as a piece of artistic work for hybrid installations, and is intrinsically related to collaborative artistic, philosophical and technological research. It has the ability to highlight temporal shifts between past and present and demonstrates how archived somatic states may ripple outwardly across technologies, bodies, and space, to audiences who embody these states within the wider somatic feld. For these MR interactions to work, methods in relation to flming, editing, and archiving are re-examined. Documentation and archiving methods are reviewed through a phenomenological lens and once distributed within the AR/MR archive installation, a postphenomenological perspective reveals how new relations with technology, materials and media are discovered. Furthermore, the use of AI is perceived as enhancing the rippling out of afective somatic states that becomes an embodied materiality1 (orig. emphasis), a relational feminist posthumanist perspective, that, permanently changes ways of seeing and experiencing dance on screens and the notion of a Screendance archive.
Keywords: Screendance; archive; installation; embodied materiality; Augmented Reality; AI